Hanukkah around the world - Lehman-Wilzig, Tami (Kar-Ben Pub., 2009)
Introduces Hanukkah, the Jewish festival of lights, and describes how it is celebrated in different areas of the world, including Israel, Istanbul, Italy, Poland, and New York City. Includes glossary and recipes.